Prinsip Amanah dalam Islam: “Perwujudan Nilai Ketuhanan dan Kemanusiaan dalam Kehidupan" - Kinana Dwinta Sukma; Meyniar Albina (Jurnal Kajian Islam dan Sosial Keagamaan, 2024)
Trust in Islam is a fundamental concept that includes divine values ​​(hablum minallah) and human values ​​(hablum minannas). As a divine value, trust symbolizes human responsibility to Allah SWT, which is manifested in worship, obedience to the Shari'a, and management of the earth as caliph. This principle is confirmed in QS. An-Nisa: 58 and QS. Al-Baqarah: 30, which links trust with justice and human obedience to God's will. By carrying out trust, humans strengthen their spiritual connection with God, maintaining the balance of nature. As a human value, amanah emphasizes the importance of moral responsibility towards fellow humans, such as upholding justice, solidarity and respect for human rights. Islam teaches that humans must maintain harmonious relationships through the practice of social justice and fair treatment of individuals and society. Recent research shows that violations of trust, such as dishonesty and overexploitation, have a negative impact on relationships between individuals and the ecosystem. Thus, trust becomes an integral element in realizing harmonious human relationships with God and others, while ensuring the sustainability of life on earth.